Culturally responsive teaching self-efficacy among education students: A cross-sectional analysis - Caingcoy, Manuel (Journal of Interdisciplinary Studies in Education, 2026)
Culturally responsive teaching self-efficacy (CRTSE) has emerged as a critical topic in the preparation of prospective teachers. Its significance has increased over time in teaching and scientific discourse. However, previous research on the CRTSE has yielded conflicting results. This cross-sectional study examined the CRTSE of education students in a teacher education institution in the Philippines. The study was conducted immediately after the participants completed the course, which is referred to as Bukidnon Cultural Studies, with Strategies in Teaching Indigenous People, which promotes culturally responsive teaching. Using a 40-item scale, forty-four education students participated in a self-assessment through purposive sampling. The results revealed that education students were highly capable or efficacious in culturally responsive teaching, except in areas such as assessment and the native language. The cross-sectional analysis revealed a significant difference in CRTSE scores between students majoring in the Filipino and English languages, particularly in terms of the classroom environment.